Predicting Skill Performance in Football Talent Identification - Ali Shafizadeh (University of Tehran, 2017)
The present study investigated the prediction of the effect and contribution of developmental and skills factors related to talent identification before football education on 10-12-year-old adolescents' skill performance after 8 educational sessions. The statistical population inclued all certified football schools in Isfshan city and finally 16 schools cooperated with the researcher. The sample included 171 male adolescents (mean±SD: age 11.01±0.79 year, height 141±7.8 cm, weight 34.03 ±7.5 kg) and 4 subjects were selected from each age group of each football school by simple random sampling method. The participants' skill performance including running with the ball, turning with the ball, dribbling and speed of running were assessed by football talent identification tests derived from the Football Association of England before and after 8 sessions of football education. Reliability of these tests were 90% and their validity was 85%. Descriptive statistics and multivariate stepwise regression analysis were used in this study. Data analysis revealed 4 models to predict adolescents' skill performance after 8 sessions of football education according to the pretests. Finally, the perfect model predicted 59.4% of variability of the critria.